EFEKTIVITAS PENERAPAN TEAM GAMES TOURNAMENT TERHADAP KETERTARIKAN BELAJAR MATEMATIKA DI SD NEGERI PANDEAN LAMPER 03 - Siti Muamanah; Setyani Safitri; Tri Agusta Ilmiawan; Kartinah; Jessica Sekar Andini (STKIP Subang, 2026)
Low interest in learning mathematics remains a common problem among elementary school students, even when supported by adequate learning facilities. This low interest is manifested in passive attitudes, a lack of enthusiasm, and low student participation in mathematics lessons. This study aims to determine the effectiveness of implementing the Team Games Tournament (TGT) learning model on the interest in learning mathematics among students in grades IVB and VB at SD Negeri Pandean Lamper 03 in Semarang. The study employs a quantitative approach using a descriptive method. The study population consists of all students in grades IVB and VB, totaling 51 students, with a total sampling technique used for data collection. Data collection was conducted through a mathematics learning interest questionnaire and an observation sheet. The questionnaire was designed based on six indicators of learning interest: interest in learning, the material and content presented, feelings of enjoyment, student engagement, student attention, and the discipline of the subject. Data were analyzed using descriptive statistics in the form of percentages and averages. The results of the study indicate that the implementation of the Team Games Tournament (TGT) model is effective in increasing students’ interest in learning mathematics, with an average percentage of 85.07%, which falls into the very high category. The highest percentage was obtained for the discipline indicator at 91%, while the lowest percentage was found in the content indicator. Meanwhile, the lowest percentage was found in the indicator of materials and content presented, at 78%. The survey results were supported by observational data showing that the implementation of the TGT model was rated as “very good.” Thus, the Team Games Tournament (TGT) model can serve as an effective learning alternative to increase elementary school students’ interest in learning mathematics.